Tradisi Intelektual Islam dan Moderasi Beragama: Peran Pesantren Tarekat Roudhoh Al-Hikam dalam Transformasi Sosial - Taufik Hidayatulloh (Journal of Religion and Social Transformation, 2026)
In recent decades, Muslim societies have faced various socio-religious challenges, including the rise of religious conservatism, the polarization of religious interpretations, and the decline of intellectual traditions in religious practice. Tarekat-based Islamic boarding schools offer a distinctive integration of Islamic scholarly education and spiritual cultivation that has the potential to shape a moderate religious character and contribute to social transformation within society. This study aims to analyze how the educational system at the Roudhoh Al-Hikam Tarekat Islamic Boarding School contributes to the development of Islamic intellectual traditions and promotes religious moderation that supports social transformation in local Muslim communities. This research employs a qualitative approach with a case study design conducted at the Roudhoh Al-Hikam Tarekat Islamic Boarding School in Bogor. Data were collected through participatory observation and in-depth interviews. The data were analyzed thematically using the theoretical framework of Terror Management Theory (TMT). The findings indicate that the educational system of the Islamic boarding school, which integrates the study of classical Islamic texts, spiritual training within the tarekat tradition, and a culture of intellectual discussion, plays a significant role in cultivating a strong Islamic intellectual tradition among students. Tarekat-based education not only enhances religious understanding but also fosters a reflective intellectual orientation, strong social ethics, and deep spiritual awareness. This study concludes that tarekat-based Islamic boarding schools play a significant role as agents of education and social transformation in Muslim societies. The integration of Islamic intellectual traditions with Sufi spiritual practices enables the development of a model of religious education that produces not only knowledgeable individuals but also individuals who embody a moderate religious outlook.